Faktor Gaya Hidup yang Berhubungan dengan Kejadian Penyakit Jantung di RSUD Sungai Dareh - Astuti Ardi Putri (Universitas Batanghari Jambi, 2019)
The high incidence of heart disease that causes deaths in the world is caused by IMA. This disease ranks third in the cause of death in developing countries. The initial mortality rate (30 days) in IMA is 30%, with more than half of deaths occurring before the patient reaches the hospital. Based on data from RSUD Sungai Dareh in 2018, there were 108 people suffering from heart disease, and as many as 43 people suffered from acute myocardial infarction. The purpose of this study was to determine lifestyle factors related to the incidence of heart disease in Sungai Dareh Hospital. The research method used is descriptive analytical design with cross sectionnal study. The number of samples of 52 people with sampling was done by accidental sampling technique. The results of this researcher were obtained, almost half 15 (28.8%) of respondents were moderate smokers. Most of the 30 (57.7%) respondents consumed foods that were at risk. And most of the respondents experienced IMA heart disease as many as 34 people (65.4%). While the results of the chi-square statistical test obtained a significance value of 5% (0.05), obtained smoking (p-value = 0,000), food (p-value = 0,000). So it can be concluded that there is a significant relationship between smoking and food with the incidence of heart disease in the Interne and Poly Room Interne at Sungai Dareh Hospital. It is expected that respondents always control blood pressure and pay attention to food and avoid smoking that causes heart disease.